Nail psoriasis treated with pulsed dye laser - Juliano Peruzzo; Gabriela Czarnobay Garbin; Gabriela Maldonado; Tania Ferreira Cestari (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Nail changes are present in about 50% of psoriasis patients and tend to be refractory to conventional treatments. Pulsed dye laser has emerged as an alternative therapy. Our aim is to evaluate the efficacy of pulsed dye laser in nail psoriasis and the impact of treatment on quality of life. Fourteen patients were treated in monthly sessions for three months. The outcome assesment was made by the Nail Psoriasis Severity Index (NAPSI). The median improvement in the scores of the overall NAPSI, nail bed NAPSI, and nail matrix NAPSI were 44.2% (P = 0.002), 50% (P = 0.033) and 65.1% (P = 0.024), respectively.